ANALISIS PENERAPAN PERENCANAAN PAJAK (TAX PLANNING) UNTUK MEMINIMALKAN BEBAN PAJAK PENGHASILAN BADAN PADA CV. XXXL - Akhmad Samhudi; Siti Raesa Rizki Pardani (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
ABSTRACTThis study aims to: (1) analze the application of tax planning in minimizing the burden of corporate income tax on CV. Bina Mandiri Banua, (2) ind out and analyze whether tax planning (tax planning) that is carried out can minimize corporate income tax compared to before CV. Bina Mandiri Banua’s tax planning.          The design of this research is a qualitative research with descriptive method. Data collection was done by interview, observation, and documentation. The result of the study indicate that tax planning carried out by bookkeeping methods, fiscal corrections, gross up methods for PPh 21 and the provision of allowances for food/drink and transportation of employees has a major influence on the magnitude of the corporate income tax burden.          The result of the analysis show that tax planning can minimize the corporate income tax burden borne by the company, in 2019 before tax planning Rp. 4.648.909,- after tax planning becomes Rp. 3.224.192,- In 2020, before tax planning, Rp. 20.571.594,- after tax planning becomes Rp. 5.989.722,- In 2021, before tax planning Rp. 10.831.213,- after tax planning to Rp. 2.671.219,-. This shows that the corporate income tax burden has been minimized, seen from the total efficiency of tax savings of Rp. 24,166,582 in the 2019-2021 period.